NILAI-NILAI PERILAKU TERHADAP SESAMA MANUSIA YANG TERCERMIN DALAM PETATAH-PETITIH DAYAK MAANYAN - B Basori; Lina Herlinawati; Nandang Rusnandar; T. Dibyo Harsono (ppjbsip, 2023)
Abstract: Dayak Ma'anyan culture (mindset, behavior patterns, and lifestyle) is reflected in the language used and the proverbs that appear in acts of communication. Proverbs have the power/power to educate, move the soul, shape attitudes, character and human character, to obtain what is revealed and radiated within oneself, and have the power as social control. The data for this study are utterances in Dayak contained in the texts of the Ma'anyan Dayak proverbs. The next analysis is the classification of data based on the form of structural aspects based on its constituent elements, the functional relationships between its constituent elements. Analysis of the proverbs in the Maanyan Dayak language contains advice, satire, praise, and diplomatic language which is often used in traditional ceremonies. The proverbs of the Dayak Ma'anyan in this study reveal many things about the behavior of the people. Among these are the behavior of the Dayak people towards the universe, towards their fellow human beings, and the attitudes and personalities of the people.